2022
DOI: 10.31234/osf.io/bd2xw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Underwhelming Pleasures: Towards a Self-Regulatory Account of Hedonic Compensation and Overconsumption

Abstract: Hedonic overconsumption (e.g., overconsumption of gratifying behaviors, e.g., eating, gaming, etc.) is common in daily life and often problematic, pointing to the need for adequate behavioral models. It has been theorized that when a consumption experience falls short of hedonic expectations people will generally consume more to compensate the shortfall. In this pre-registered experience sampling study we test this idea empirically via our hedonic compensation model, and we examine whether distraction during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…This tendency for increased consumption resulting from activated yet unsatisfied expectations has been noted in other contexts associated with hedonic benefits. Murphy et al (2022) enrolled 220 participants and administered 7 surveys per day for 7 days to investigate the relationship between unmet demand and subsequent consumption. Their study revealed that when individuals are distracted during hedonic consumption, their enjoyment of the consumption decreases in comparison to expected values, resulting in dissatisfaction and a greater tendency for overconsumption.…”
Section: Consumer Spending On Offline Movies Post-subscriptionmentioning
confidence: 99%
“…This tendency for increased consumption resulting from activated yet unsatisfied expectations has been noted in other contexts associated with hedonic benefits. Murphy et al (2022) enrolled 220 participants and administered 7 surveys per day for 7 days to investigate the relationship between unmet demand and subsequent consumption. Their study revealed that when individuals are distracted during hedonic consumption, their enjoyment of the consumption decreases in comparison to expected values, resulting in dissatisfaction and a greater tendency for overconsumption.…”
Section: Consumer Spending On Offline Movies Post-subscriptionmentioning
confidence: 99%